On the significance of economic structure and regional innovation systems for the foundation of knowledge-intensive business services - Thomas Stahlecker; Andreas Koch (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2004)
The shift to new forms of knowledge creation reflects a remarkable increase in the number of knowledge-intensive business service firms (KIBS). KIBS are believed to be one of the main drivers of technological change and economic progress and can be described as users, carriers and sources of innovation (Miles et al. 1995). In addi-tion to macroeconomic implications, newly founded KIBS are considered to play an important role within regional production and innovation systems. As firm founders in early stages of their firms' development mostly draw on regional resources and as KIBS acquire knowledge in the course of the interactive process that takes place when the service is provided, an intense interdependency between the regional economic, technological and institutional set-up and newly founded KIBS can be supposed. Within these processes of inter-relationship, proximity between the different actors of the particular innovation and production system clearly matters.However, as entrepreneurship research has hardly ever investigated KIBS and re-search into the role of KIBS in processes of regional change has just begun, this con-tribution analyses the inter-relationships between KIBS foundations and actors within the respective innovation and production system. In a qualitative and conceptual way, in-depth studies of three German metropolitan regions with regard to the foundation of KIBS will be outlined. The results indicate that the necessity to adapt regional structures goes hand in hand with an exploitation of regional knowledge and the crea-tion of bridging institutions in the shape of KIBS foundations.
urn:nbn:de:0011-n-211845
Keywords: 330; Unternehmensgründung; Unternehmensdienstleistung; Wissen; Regionalpolitik; Innovationspolitik; Bremen (Stadt); Deutschland; Stuttgart (Region); München (Region)